Multi-Omics Profiling Specifies Involvement of Alternative Ribosomal Proteins in Response to Zinc Limitation in Mycobacterium smegmatis - Dow, Allexa; Burger, Andrew; Marcantonio, Endrei; Prisic, Sladjana (Frontiers in Microbiology, 2022)
Zinc ion (Zn2+) is an essential micronutrient and a potent antioxidant. However, Zn2+ is often limited in the environment. Upon Zn2+ limitation, Mycolicibacterium (basonym: Mycobacterium) smegmatis (Msm) undergoes a morphogenesis, which relies on alternative ribosomal proteins (AltRPs); i.e., Zn2+-independent paralogues of Zn2+-dependent ribosomal proteins. However, the underlying physiological changes triggered by Zn2+ limitation and how AltRPs contribute to these changes were not known. In this study, we expand the knowledge of mechanisms utilized by Msm to endure Zn2+ limitation, by comparing the transcriptomes and proteomes of Zn2+-limited and Zn2+-replete Msm. We further compare, corroborate and contrast our results to those reported for the pathogenic mycobacterium, M. tuberculosis, which highlighted conservation of the upregulated oxidative stress response when Zn2+ is limited in both mycobacteria. By comparing the multi-omics analysis of a knockout mutant lacking AltRPs (ΔaltRP) to the Msm wild type strain, we specify the involvement of AltRPs in the response to Zn2+ limitation. Our results show that AltRP expression in Msm does not affect the conserved oxidative stress response during Zn2+ limitation observed in mycobacteria, but AltRPs do significantly impact expression patterns of numerous genes that may be involved in morphogenesis or other adaptive responses. We conclude that AltRPs are not only important as functional replacements for their Zn2+-dependent paralogues; they are also involved in the transcriptomic response to the Zn2+-limited environment.